Stock market volatility and exchange rate regime in Malaysia: a preliminary analysis / Noor Zahirah Mohd Sidek, Norridzwan Abidin and Azli Umar - Mohd Sidek, Noor Zahirah; Abidin, Norridzwan; Umar, Azli (Universiti Teknologi MARA, Kedah, 2011)
The choice of exchange rate regime and its possible impact on economic performance has recently become a new area of interest amongst both economists and policy makers. The study on the impact of exchange rate regime on financial performance, however, is relatively scarce, partly due to theoretical ambiguity and the definition of financial performance itself. Hence, this study intends to fill this gap by focusing on the stock return volatility of selected stock return indices in Malaysia over different exchange rate regimes. Specifically, the objective of this paper is to examine the impact of exchange rate regime on selected stock market return volatility. We draw on GARCH(1,1) to capture volatility clustering phenomenon. Results suggest that stock return is less volatile during managed float for Trade and Services, Construction and Finance stock return indices only. The Plantation stock return index, on the other hand, exhibits more volatility during managed float period.